Penegakan Hukum Terhadap Korporasi Yang Melakukan Pencucian Uang Dari Hasil Korupsi Di Indonesia - Effendy Nasution, Fachreja; Kristiawanto, Kristiawanto; T. Paparang, Santrawan (Jurnal Syntax Fusion, 2022)
Law enforcement against the crime of laundering committed by corporations, has not been carried out optimally. This is because there are no legal rules that clearly regulate the form of corporate responsibility as a subject of criminal law and the low understanding of law enforcement in understanding existence as a subject of criminal law. Based on this background, the research formulated the problem of how to prove the mechanism of money laundering crimes committed by corporations in corruption crimes in Indonesia, as well as how to enforce the law against corporations that commit money laundering crimes in corruption crimes in Indonesia. The method used in this research is normative legal research by using secondary data sourced from primary, secondary and tertiary legal materials which were analyzed using qualitative juridical analysis methods. From the research results, it can be seen that the proof of money laundering crimes committed by corporations is based on corporate criminal responsibility as stipulated in Article 6 of Law no. 8 year 2010 on ML. The government together with the DPR must immediately formulate and make regulations regarding corporate criminal liability as a legal subject for criminal acts, especially in the Criminal Procedure Code (RUU-KUHAP). So that law enforcement against corporate crimes, especially money laundering crimes committed by corporations can have legal certainty.